The Effect of Feeding Starter Diets for Different Periods on Performance ‎of Broilers - Baha Eddin Abu-Bakr (My University, 2003)
A total of 150 birds were used in this experiment in summer 2002 to investigate the effect of feeding starter diets for different periods on the performance and the economical advantages on broiler chicks. Birds were fed starter diets for two, three and four weeks prior to feeding the finisher diets. Birds fed the starter for four weeks had higher (p

تم استخدام 150 طيرا من صيصان اللحم بشهري تموز – اب 2002 لدراسة مدى تأثير التغذية بعلف بادئ لفترات مختلفة على زيادة الوزن النهائي والتكلفة الاقتصادية، حيث غذيت الصيصان على علف بادئ فترة اسبوعين، ومجموعة ثانية فترة ثلاثة اسابيع، ومجموعة ثالثة فترة اربعة اسابيع، قبل تغذيتها على علف نهائي حتى عمر 42 يوما. وجد أن تغذية الصيصان على العلف البادئ لمدة أربعة أسابيع، أدت إلى زيادة معنوية (p
تأثير تغذية صيصان اللحم بعلف بادئ لفترات مختلفة على زيادة الوزن النهائي